Mutations in a Highly Conserved Motif of nsp1? Protein Attenuate the Innate Immune Suppression Function of Porcine Reproductive and Respiratory Syndrome Virus - Li, Yanhua; Shyu, Duan-Liang; Shang, Pengcheng; Bai, Jianfa; Ouyang, Kang; Dhakal, Santosh; Hiremath, Jagadish; Binjawadagi, Basavaraj; Renukaradhya, Gourapura J.; Fang, Ying (My University, 2016)
Porcine reproductive and respiratory syndrome virus (PRRSV) nonstructural protein 1? (nsp1?) is a multifunctional viral protein, which is involved in suppressing the host innate immune response and activating a unique ?2/?1 programmed ribosomal frameshifting (PRF) signal for the expression of frameshifting products. In this study, site-directed mutagenesis analysis showed that the R128A or R129A mutation introduced into a highly conserved motif (123GKYLQRRLQ131) reduced the ability of nsp1? to suppress interferon beta (IFN-?) activation and also impaired nsp1?'s function as a PRF transactivator. Three recombinant viruses, vR128A, vR129A, and vRR129AA, carrying single or double mutations in the GKYLQRRLQ motif were characterized. In comparison to the wild-type (WT) virus, vR128A and vR129A showed slightly reduced growth abilities, while the vRR129AA mutant had a significantly reduced growth ability in infected cells. Consistent with the attenuated growth phenotype in vitro, pigs infected with nsp1? mutants had lower levels of viremia than did WT virus-infected pigs. Compared to the WT virus in infected cells, all three mutated viruses stimulated high levels of IFN-? expression and exhibited a reduced ability to suppress the mRNA expression of selected interferon-stimulated genes (ISGs). In pigs infected with nsp1? mutants, IFN-? production was increased in the lungs at early time points postinfection, which was correlated with increased innate NK cell function. Furthermore, the augmented innate response was consistent with the increased production of IFN-? in pigs infected with mutated viruses. These data demonstrate that residues R128 and R129 are critical for nsp1? function and that modifying these key residues in the GKYLQRRLQ motif attenuates virus growth ability and improves the innate and adaptive immune responses in infected animals.
Citation: Li Y, Shyu D-L, Shang P, Bai J, Ouyang K, Dhakal S, Hiremath J, Binjawadagi B, Renukaradhya GJ, Fang Y. 2016. Mutations in a highly conserved motif of nsp1? protein attenuate the innate immune suppression function of porcine reproductive and respiratory syndrome virus. J Virol 90:3584–3599. doi:10.1128/JVI.03069-15.